Machine Learning-based Intelligent Smart Warning System in Twisty Swerve in Hill Station using IoT - S, Gnanamurugan; S, Badmapriya; S, Boomikadevi; M, Kiruthiga; M, Mathumitha (Journal of Trends in Computer Science and Smart Technology, 2023)
The surveyed reports state that about 10% of car accidents in the hilly areas happen on curved roads. It is risky to drive through curves and bends. Therefore, this work suggests a hairpin bend road collision prevention system using Internet of Things (IoT). The proposed design employing IoT strives to prevent the collisions by initiating warning alarms on detecting vehicles on the either side of the hairpin bend. The detection of the vehicles in the either side is performed using an ultrasonic sensor.